2019
DOI: 10.1002/er.4502
|View full text |Cite
|
Sign up to set email alerts
|

Modification on hydrated salt‐based phase change composites with carbon fillers for electronic thermal management

Abstract: Summary For electronic thermal management with hydrated salt phase change materials (PCM), supercooling and thermal stability usually inhibit its development. In view of this, novel of disodium hydrogen phosphate dodecahydrate (DSP)‐based composites PCM with miniaturized size is developed to solve these problems. Three kinds of carbon fillers employed as both nucleating agent and heat transfer promoter were added in DSP separately. The influences of carbon fillers' specific surface area, particle size, and ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Salt and salt hydrates are abundant sources in salt lakes or seawater, therefore it is cost-competitive with a price of one percent of paraffin. The fair cost and non-flammable characteristics of inorganic phase change materials provide much greater encouragement for commercialization than organics [25]. Salt…”
Section: Inorganic Pcmsmentioning
confidence: 99%
“…Salt and salt hydrates are abundant sources in salt lakes or seawater, therefore it is cost-competitive with a price of one percent of paraffin. The fair cost and non-flammable characteristics of inorganic phase change materials provide much greater encouragement for commercialization than organics [25]. Salt…”
Section: Inorganic Pcmsmentioning
confidence: 99%
“…which means that the heat transfer is controlled by the film. Finally, it is interesting to compare the stationary power predicted by Equation (10) using a film layer and the power from traditional approaches, that is, by direct contact of the solidified layer with the wall and its continuous growth given by Equation (1). By dividing Equation (10) with Equation (1) one obtains the ratio between the density powers as…”
Section: Attainable Power Using Film Heat Transfer and Gravitationamentioning
confidence: 99%
“…Those techniques of heat transfer enhancement based in adapted geometric configurations and extended surfaces; and those techniques in which heat transfer enhancement is attained by directly modifying in some way the thermal conductivity of the PCM. In the first category we have, for example, the use of fins, heat pipes, or fillers, and in the second category we have the use of encapsulation; or microencapsulation of the PCM as well as the use of nanoparticles including nanotubes or nanocomposites . There are copious available literature of the topic and specially in the last advancements in PCMs, and for the interested reader on various techniques of heat transfer enhancement in latent heat thermal energy storage systems it is recommended the up‐to‐date review on the state‐of‐the‐art as well as critical review …”
Section: Introductionmentioning
confidence: 99%
“…But it is believed that large number of nucleating centers, and thus high heterogeneous nucleation rate, are beneficial for the suppression of supercooling. 4,[24][25][26] For example, the supercooling of ME could be decreased to 64°C due to the graphitic surface of graphite foams, and carbon nanotubes provided a great number of nucleating centers. 19 Wang et al 4 also found that the supercooling of ME could be decreased by 83.6% with the help of silica shell with high surface area and the restricted molecular movement caused by a thickener.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is expectable that form-stable PCMs, in which sugar alcohols and polymers act as solid-liquid PCMs and supporting materials, respectively, can exhibit high latent heat storage capacity. 4,[24][25][26] For example, the supercooling of ME could be decreased to 64°C due to the graphitic surface of graphite foams, and carbon nanotubes provided a great number of nucleating centers. For example, the melting points of ME and D-mannitol are about 118°C and 166°C, respectively.…”
mentioning
confidence: 99%